Artificial Intelligence on Journalism: Algorithmic Power Targeting the Crack in Memory in the Example of ‘Religious Wave’ Terrorist Attacks - Fikriye Çelik (Medya ve Din Araştırmaları Dergisi)
The digital technology that governs this historical process is a partner in the creation of an ambiguous world with its image attached to everyday life forms. This picture the world is trapped in is becoming clearer in journalism practices. As the sector becomes acquainted with new forms of journalism, the responsibility of the news reader to be a truth reader increases. AI is visible in news production, from access to the source to the production. This study emerged from the necessity of considering the news-power-technology relationship and the memory distortion dynamics of global power structures together. In this study, which aims to point out the risks of AI news in the context of memory distortion, the ‘religious wave’ terrorist attacks are taken into consideration. Critical discourse analysis was used in this research conducted on a sample of the ChatGPT’s news regarding 9/11, 7/7, 2015 Paris and Christchurch attacks. The findings show that the discourse of global power is repeated in artificial intelligence news on religion-based terrorist attacks and that technology targeting social memory reproduces the ideology of power. Accordingly, an intensive reading practice can be recommended to the interlocutors of the news against the news emerging from AI algorithms.